Early detection of SARS-CoV-2 without human intervention to combat COVID-19 using drone technology. Issue 1 (8th December 2020) - Manigandan, Sekar; Thaloor Ramesh, Praveen Kumar; Chi, Nguyen Thuy Lan; Brindhadevi, Kathirvel
Abstract : Purpose: The focus of the current study to combat the ongoing pandemic by preventing the transmission using the Unmanned aerial vehicle system. The transmission of the COVID-19 pandemic can be avoided only by finding the infectious person at the right time. Despite the thermal scanning camera and artificial intelligence technology, finding the infectious individual at many occasions has become questionable. Design/methodology/approach: The drones are equipped with the thermal vision camera to detect the human body temperature. In addition, they are equipped with the disinfect tank to sanitize the indoor and outdoor environments based on the requirement. Findings: Once the lockdown eased, the experts fear that the infection rate can increase in the high-density population countries such as India. The drone with thermal screening and day vision camera can detect the infection of the person without any human intervention. Further, they can also be used to disinfect the public places by aerial spraying. Practical implications: Using the drones to monitor the work places, shopping mall and education institution to identify the mask through artificial intelligence is viable without human intervention in short span of time. Originality/value: COVID-19 impact on the global was awful. Finding a suitable technology to combat the COVID-19 is much necessary. This conceptual study proposed to use drone technology to identify the infection at right time even on densely populated streets. Further, artificial technology can be used to detect the person who was not wearing mask. Added to above, disinfect tank can be mounted to sanitize the area in the required places.